Huntington Beach 4th of July Parade with Watkins Family and Model T Ford - Watkins, Howard::::::::: (1988)
Howard Watkins wearing Cherokee Indian headdress, Albert Watkins, Robin Watkins wearing headdress, Frances Kamp, Adam Watkins, Rose O'Reilly, Carol, and Jerry Kamp